1998
DOI: 10.1046/j.1365-2893.1998.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis G infection: role in cryptogenic chronic liver disease and primary liver cell cancer in the UK

Abstract: Hepatitis G virus (HGV) is a flavivirus that can cause acute hepatitis and persistent infection but its role in chronic liver disease or primary liver cancer is unproven. In this study we have examined the prevalence of HGV RNA in the serum of patients with hepatitis C virus (HCV) infection and in patients with cryptogenic chronic liver disease, including non-alcoholic steatohepatitis (NASH), and in patients with HCV-related hepatocellular carcinoma (HCC) and HCC arising in patients with cryptogenic liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Hepatitis G virus (GBV‐C, HGV), identified in 199672 and TT virus (TTV), identified in 199773 have also been examined for a relationship with PLC. Although HGB was significantly associated with PLC in some studies,56, 74 others have reported little if any association 40, 44, 55, 75–78. TTV has been examined in a number of studies, but no significant association with PLC has yet been reported 79–84…”
Section: Discussionmentioning
confidence: 98%
“…Hepatitis G virus (GBV‐C, HGV), identified in 199672 and TT virus (TTV), identified in 199773 have also been examined for a relationship with PLC. Although HGB was significantly associated with PLC in some studies,56, 74 others have reported little if any association 40, 44, 55, 75–78. TTV has been examined in a number of studies, but no significant association with PLC has yet been reported 79–84…”
Section: Discussionmentioning
confidence: 98%
“…Since its discovery, the primary site(s) of replication and cellular receptors for HPgV has (have) not been identifi ed and a correlation with non-A/non-E hepatitis remains a controversial issue even though HPgV RNA has been detected more frequently in patients with acute and chronic non-A/non-E hepatitis than in healthy subjects. Early studies indicated that the virus was hepatotropic (Grassi et al, 2000;Hollingsworth et al, 1998;Guilera et al, 1998), although numerous studies carried out since the late 1990s, have shown that HPgV is not hepatotropic or only barely detectable in the liver of infected individuals (Pessoa et al, 1998;Chivero et al, 2014). Th e virus can persist for at least one month in culture in peripheral blood mononuclear cells (PBMCs) from infected individuals (Th ézé et al, 2015;Chivero and Stapleton, 2015).…”
Section: Clinical Relevance Of Hpgv Infectionmentioning
confidence: 99%
“…In the context of recently published studies [3,[15][16][17][18][19] an etiologic role of GBV-C/HGV cannot be excluded in a minority of non-A-E hepatitis cases. Thus, the testing for HGV may be a useful extension of the diagnostic procedure for non-A-E hepatitis.A possible benefit of interferon alpha treatment that suppresses GBV-C/HGV replication effectively [20,21] should be discussed for patients with cryptogenic hepatitis and GBV-C/HGV viremia.The controversial data of other authors may be due to different study designs [13,22,23], geographical differences [8], or to insignificant associations due to the small number of individuals examined [24].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, GBV-C/HGV appears to be well adapted to the human host and its importance as a viral pathogen has been questioned. Recently published data suggest that GBV-C/HGV may play a role in the pathogenesis of acute non-A-E hepatitis [7], but not in chronic cryptogenic liver disease or hepatocellular carcinoma [8,9].Additionally, GBV-C/HGV is associated with non-Hodgkin's lymphoma [10], but its association with other extrahepatic malignancies is unclear [11]. The aim of this study was i) to determine the prevalence of anti-GBV-C/HGV antibodies and GBV-C/HGV RNA in traumatologic outpatients as a control group for further epidemiological studies, ii) to examine GBV-C/HGV prevalences in chronic non-A-E hepatitis patients and iii) in a group of patients suffering from extrahepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%